Pengaruh Komposisi Dewan Komisaris terhadap Nilai Perusahaan dengan Leverage Sebagai Variabel Intervening - Regina Febby; Saarce Elsye Hatane (Business Accounting Review, 2017)
This research aimed to know the influence of Board Composition as measured by the proportion of independent Board of Commissioners toward the Firm Value as measured by the simplified formula of Tobin's Q by Chung and Pruitt (1994). The study also used leverage as intervening variable. This research used a sample of the consumer goods sector companies (sub-sectors, cigarette, pharmaceuticals, cosmetics and household, household appliances, along with food and drink) and trade sector companies (wholesale and retail sub-sectors) listed in the Indonesia stock exchange in the period of 2010-2015. The samples were selected by using purposive sampling method, and obtained from sample of 44 companies. The results of this study indicated that the proportion of the independent Board of Commissioners had significant positive influence toward firm value and also had significant negative influence toward leverage. There was significant negative influence between leverage toward firm value. This research also showed that leverage could not mediate the relationship between the independent board and firm value.